Midlife lipid and glucose levels are associated with Alzheimer's disease. Issue 1 (23rd March 2022) - Zhang, Xiaoling; Tong, Tong; Chang, Andrew; Ang, Ting Fang Alvin; Tao, Qiushan; Auerbach, Sanford; Devine, Sherral; Qiu, Wei Qiao; Mez, Jesse; Massaro, Joseph; Lunetta, Kathryn L.; Au, Rhoda; et al.
Abstract: Introduction: It is unknown whether vascular and metabolic diseases assessed in early adulthood are associated with Alzheimer's disease (AD) later in life. Methods: Association of AD with lipid fractions, glucose, blood pressure, body mass index (BMI), and smoking obtained prospectively from 4932 Framingham Heart Study (FHS) participants across nine quadrennial examinations was evaluated using Cox proportional hazard and Kaplan‐Meier models. Age‐, sex‐, and education‐adjusted models were tested for each factor measured at each exam and within three adult age groups (early = 35‐50, middle = 51‐60, and late = 61‐70). Results: A 15 mg/dL increase in high density lipoprotein (HDL) cholesterol was associated with decreased AD risk during early (15.4%, P = 0.041) and middle (17.9%, P = 0.014) adulthood. A 15 mg/dL increase in glucose measured during middle adulthood was associated with 14.5% increased AD risk ( P = 0.00029). These findings remained significant after adjusting for treatment. Discussion: Our findings suggest that careful management of cholesterol and glucose beginning in early adulthood can lower AD risk.